Penerapan fungsi public relation guna membangun citra dan kepuasan pelanggan - Dewaji, Jannara (Maliki Interdisciplinary Journal, 2023)
This research aims to investigate the implementation of public relations functions in building a positive image and customer trust in the context of laundry service business, with a case study on Laundry 22. Through literature review and interviews with the Laundry 22 operators, the study examines the role of PR functions in shaping the business image. The research also notes several successful PR strategies employed, such as using WhatsApp for communication, offering discounts on Fridays, and providing pickup and delivery services. By employing an appropriate PR approach, Laundry 22 has successfully built an image as a reliable, sustainable laundry service provider that caters to customer needs. This research outlines several PR functions that Laundry 22 has executed to build customer trust and a positive image. The research findings indicate that Laundry 22 demonstrates its commitment to building a positive image and sustained trust through communication, discounts, and pickup and delivery services.